Self‐Assembled Peptide–Polyfluorene Nanocomposites for Biodegradable Organic Electronics. Issue 14 (7th August 2015) - Khanra, Soma; Cipriano, Thiago; Lam, Thomas; White, Tommi A.; Fileti, Eudes E.; Alves, Wendel A.; Guha, Suchismita
<x xml:space="preserve">Abstract</x> Based on self‐assembly and mimicking strategies occurring in nature, peptide nanomaterials play a unique role in a new generation of hybrid materials for the electronics of the 21st century. This report describes the functionalization of diphenylalanine (FF)‐based micro/nanostructures with blue‐emitting conducting polymers of the polyfluorene (PF) family. The FF:PF polymer nanocomposites are synthesized by a liquid‐vapor phase method. Electron microscopy images reveal di‐octyl‐substituted PF (PF8) to bind better to the FF micro/nanotubes in comparison with ethyl‐hexyl PF (PF2/6), which influences its optical properties. Molecular dynamics simulations of FF nanotubes with monomeric units of PFs show that PF8 favors greater proximity to the grooves on the surface of the nanotubes due to a higher van der Waals interaction energy compared to PF2/6. The FF:PF nanocomposites are further utilized in light‐emitting diodes. Biodegradability tests from FF:PF8 nanocomposite films show more than 80% weight loss in 2 h by enzymatic action compared to PF8 pristine films, which do not degrade. Self‐assembly of FF nanostructures with organic semiconductors opens up a new generation of biocompatible and biodegradable materials in organic electronics.